2021
DOI: 10.1101/2021.02.28.433255
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spatial alanine metabolism determines local growth dynamics ofEscherichia colicolonies

Abstract: Bacteria commonly live in spatially structured assemblages encased by an extracellular matrix, termed biofilms. Metabolic activity of the cells inside biofilms causes gradients in local environmental conditions, which leads to the emergence of subpopulations with different metabolism. Basic information about the spatial arrangement of such metabolic subpopulations, as well as their interaction strength and interaction length scales are lacking, even for model systems like biofilms of Escherichia coli grown as … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 85 publications
0
8
0
Order By: Relevance
“…Indeed, there has been a growing appreciation for the important role of amino acids as carbon sources; however, there has also been an emphasis on investigating the regulatory functions of certain amino acids. Investigations into E. coli biofilm formation revealed the spatiotemporal regulation of L-Alanine metabolism is essential for cell viability and growth of colonies [57], whereas conversely, catalysis of the amino acid L-Tryptophan was implicated with the inhibition of biofilm formation [58]. In the mammalian host, sensing these metabolites can serve as stimuli to trigger the expression of essential virulence genes.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, there has been a growing appreciation for the important role of amino acids as carbon sources; however, there has also been an emphasis on investigating the regulatory functions of certain amino acids. Investigations into E. coli biofilm formation revealed the spatiotemporal regulation of L-Alanine metabolism is essential for cell viability and growth of colonies [57], whereas conversely, catalysis of the amino acid L-Tryptophan was implicated with the inhibition of biofilm formation [58]. In the mammalian host, sensing these metabolites can serve as stimuli to trigger the expression of essential virulence genes.…”
Section: Discussionmentioning
confidence: 99%
“…This has also been demonstrated for sessile biofilms, where growth substrates can have profound effects on biofilm morphology, growth dynamics, and mechanical properties [16, 17, 18, 19]. Recent studies on single-species biofilms have identified crossfeeding mechanisms for acetate, alanine and other nutrients influencing biofilm viability and morphology [20, 21, 22]. Emergent biofilm properties have also been found to give rise to water and nutrient transport mechanisms [23, 24, 25], yet the factors governing how they form and how environmental cues govern their structure are currently unknown.…”
Section: Introductionmentioning
confidence: 98%
“…Altering the nutrient substrate upon which a biofilm grows can illicit profound changes in biofilm morphology, growth dynamics, and mechanical properties [16,17,18,19]. Changing the bulk carbon or nitrogen concentration of growth media can alter pattern formation within biofilms [4,20,21], and recent studies on single-species biofilms have identified cross-feeding mechanisms for acetate [22] and alanine [23]. Additionally, varying substrate stiffness has been linked to altered attachment [24,25], motility [8], growth dynamics [26], and expansion [27] of biofilm constituent cells.…”
Section: Introductionmentioning
confidence: 99%
“…[ 18 ] Cells encased in the EPS can take advantage of the close proximity to their neighbors through the acquisition, exchange, and recycling of nutrients and stress protectants. [ 19,20 ] The cells can benefit via division of labor during biofilm matrix production, [ 21 ] and by integrating their collective behavior through the synthesis of signaling molecules (e.g., quorum sensing) [ 22 ] and potassium‐dependent electric currents, [ 23–25 ] processes that will also allow the timely production of virulence factors by pathogenic microorganisms. [ 21 ] Moreover, biofilms also facilitate horizontal gene transfer between the cells via conjugation, transduction and transformation, as biofilms cannot only be formed by members of a single microbial species but can also comprise multi‐species assemblages.…”
Section: Introductionmentioning
confidence: 99%
“…[ 26,27 ] Furthermore, different chemical (e.g., oxygen, water, salt, and nutrients) and mechanical gradients formed within the biofilm generate heterogeneous microenvironments leading to special cellular adaptation responses of the individual cell. [ 20,23 ] In contrast to single cells, a biofilm can be seen as a collection of highly differentiated microorganisms that cooperate for the common good of the population through interconnected cellular responses and developmental programs. However, there is also intense competition between members of the biofilm.…”
Section: Introductionmentioning
confidence: 99%